Daratumumab-based salvage therapy enables umbilical cord blood transplantation in multiline refractory, elderly T-lymphoblastic lymphoma: a case report - Yang, Qian; Yang, Lei; Cai, Ping; Ji, Yong-hui; Zhou, Jing-dong; Qian, Jun (Frontiers in Immunology, 2026)
While patients with T-lymphoblastic lymphoma (T-LBL) now generally have a favorable prognosis, with 3-year event-free survival rate approaching 69.2%, refractory T-LBL in older adults is almost invariably fatal, exhibiting a dismal 5-year overall survival rate of only 4%. This poor prognosis is exacerbated by frequent exclusion from cellular therapies like CD7 CAR T-cell trials. We report a case of a 60-year-old man with multi-refractory T-LBL exhibiting a partial response to hyper-CVAD followed by progression on venetoclax plus azacitidine. This patient achieved complete remission after a single cycle of DMPD salvage therapy comprising daratumumab, liposomal mitoxantrone, pegaspargase and dexamethasone. This readily accessible regimen circumvented the manufacturing delays and prohibitive costs associated with CAR T-cell platforms. It successfully bridged the patient to double umbilical cord blood transplantation, resulting in full donor chimerism by day +21 and sustained remission despite post-transplant complications. The remarkable efficacy observed in this refractory T-LBL case, contrasting sharply with historical treatment outcomes, suggests that the DMPD regimen may serve as both an immediately actionable and potentially definitive therapeutic approach for elderly patients who are ineligible for hematopoietic stem cell transplantation.